Knowledge and practices on prevention of coronary artery diseases in nepalese community: A cross-sectional from five different cities in Nepal - Bhattarai, Sunita Pokharel; Neupane, Pushpa (Nepalese Heart Journal, 2018)
Background and Aims: The incidence of cardiovascular diseases (CVDs) is rapidly increasing at an alarming rate worldwide. This study aimed to identify the knowledge and practices of coronary artery diseases.Method: A cross sectional study and a purposive sampling method was used to select the cities and five different cities of Nepal were selected for this study. Literate people, one who can fill the questionnaire, voluntarily participated for this study during the free cardiac health camp organized by Shahid Gangalal National Heart Center. Total 356 participants participated in this study.Results: This study reveals that one fourth (22.5%) of the participants had excellent knowledge and 32.6% were with poor knowledge regarding the prevention of CAD (coronary artery disease), whereas one fifth had no risk factors of CAD and half of them had 2-3 risk factors. Maximum six risk factors were present only on 0.6%, regarding the practices, 31.7% of them monitored blood pressure at least once, (92.1%) haven’t had the blood sugar test yet whereas only 7.9% had lab test to monitor the blood sugar and blood cholesterol was done by 3.9%.Conclusion: This study concludes with the poor knowledge and practices on CAD. Awareness programs can help people to be aware of risk factors of CAD.